2000
DOI: 10.1016/s0020-7683(00)00200-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of mode I crack growth in polymers by crazing

Abstract: Crazing in amorphous polymers under mode I loading conditions is simulated using the concept of embedded cohesive surfaces with a recently proposed model. The dependence of the predicted crack growth resistance on the crazing material parameters is studied. In general, for constant loading rate, a lower fracture toughness is predicted for shorter craze lengths. However, since the widening of the craze is of a viscoplastic nature, this trend can be reversed for increasing loading rate. The parameter variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Furthermore, interface elements are placed between the fibres and the epoxy matrix. This modelling approach, which was originally proposed by Xu and Needleman [15], has been successfully used in failure analyses of various materials, such as crazing in polymers [16], and quasi-brittle fracture in cementitious materials [17].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Furthermore, interface elements are placed between the fibres and the epoxy matrix. This modelling approach, which was originally proposed by Xu and Needleman [15], has been successfully used in failure analyses of various materials, such as crazing in polymers [16], and quasi-brittle fracture in cementitious materials [17].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Studies on the mechanism of crazing have suggested that the nucleation of craze initiates with the formation of deformation bands, and the growth occurs by a process that involves existing voids advance finger-like extensions into the bulk polymer, linking up the stretched fibrils in their wake [20,21]. Furthermore, electron microscopy studies indicated that in the craze zone, in addition to the main fibrils that are present normal to the orientation of a craze and bridge the two surfaces, cross-tie fibrils are also present, which link the main fibrils [22]. Other dominant micromechanisms proposed for stress whitening include shear deformation bands, kinking, microcracking, and ductile ploughing.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical behavior of polymer composites reinforced with particles is complex mainly because it is affected by a great number of parameters, such as: (1) particle stiffness, (2) particle-matrix interphase, 9,11 (3) particle-matrix bond strength, (4) filler concentration, 11 (5) particle agglomeration, 17,18 (6) strain magnification, (7) dewetting, 19-21 (8) particle distribution, 11 (9) crazing, 22,23 and (10) degree of mixing. Filler particles act as stress concentrators and a nonuniform stress field is obtained in a stressed sample.…”
Section: Modelingmentioning
confidence: 99%